A study on the manifestation of Islamic value in contemporary womens' fashion in Malaysia / Norzaleha Zainun - Zainun, Norzaleha (2014)
This thesis is about contemporary Islamic wear in Malaysia. Contemporary Islamic wear designs are rapidly flooding the country and are mostly not covering the aurah. The awareness of the concept of aurah among Muslim's women in this country is quiet high. Thus, providing many opportunities for fashion designers to produce contemporary Islamic wear. The contemporary fashion is so dominant that it hindered the need for an Islamic fashion design. Fashion designers is competing among each other to create contemporary Islamic wear, but unfortunately their designs are more towards creating attention then manifesting the knowledge of aurah in Islam. This study focused on contemporary Islamic wear in the Islamic Fashion Festival (IFF) produced by Malaysian fashion designers. The basis for the research is from the Al-Quran, Al-Sunnah and Al-Hadith, The analysis is from the art historical method touching on the form and content of the 30 samples from the IFF. The finding shows that most of the works produced by the IFF were not truly following the Islamic concept of dressing. Hence, from the detailed analysis, Islamic dress codes were designed as guideless for the Islamic fashion industry. At this stage, IFF ' effort in promoting Islamic wear is commendable but it could be better if they totally understand the concept of aurah in Islam and following the stipulated Islamic dress codes. Wallah'ualam. Insya' Allah.